Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/17470218.2013.793732
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity and Oversensitivity to Answer Diagnosticity in Hypothesis Testing

Abstract: Two experiments examined how people perceive the diagnosticity of different answers ("yes" and "no") to the same question. We manipulated whether the "yes" and the "no" answers conveyed the same amount of information or not, as well as the presentation format of the probabilities of the features inquired about. In Experiment 1, participants were presented with only the percentages of occurrence of the features, which most straightforwardly apply to the diagnosticity of "yes" answers. In Experiment 2, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 70 publications
(201 reference statements)
0
16
0
Order By: Relevance
“…We tested the differences between presenting information with complement (e.g., 70% of turtles are Bayosian and 30% of turtles are Freqosian) and presenting information without complement (e.g., 70% of turtles are Bayosian). Rusconi and McKenzie (2013) have shown that the inclusion of complement information with the standard probability format improved sensitivity to the informativeness of an answer, which we hypothesized would also be helpful for making search decisions. This design feature was not manipulated in the visual formats, all of which intrinsically include complement information.…”
Section: Information Search Scenariomentioning
confidence: 96%
“…We tested the differences between presenting information with complement (e.g., 70% of turtles are Bayosian and 30% of turtles are Freqosian) and presenting information without complement (e.g., 70% of turtles are Bayosian). Rusconi and McKenzie (2013) have shown that the inclusion of complement information with the standard probability format improved sensitivity to the informativeness of an answer, which we hypothesized would also be helpful for making search decisions. This design feature was not manipulated in the visual formats, all of which intrinsically include complement information.…”
Section: Information Search Scenariomentioning
confidence: 96%
“…According to the authors, cue diagnosticity is an emergent property of cue frequency, and thus a rare cue is more informative than a common cue. Rather than diagnosticity as defined in the category learning theory, the latter conceptualization refers more squarely to the constructs of "surprisal" (Tribus, 1961), "self-information" in information theory (Rusconi, Crippa, Russo, & Cherubini, 2012), and the "rarity assumption" in the Bayesian reasoning literature (Anderson, 1990;McKenzie, 2006;McKenzie & Chase, 2012;McKenzie & Mikkelsen, 2000Oaksford & Chater, 1994;Rusconi & McKenzie, 2013), whereby "answers, or test outcomes, are diagnostic to the extent that they are rare or surprising" (McKenzie, 2006, p. 580). Future work should differentiate the terminology used to define the constructs of diagnosticity as emerged from the categorization literature and diagnosticity as defined in the information-theory field.…”
Section: Frequency and Diagnosticitymentioning
confidence: 99%
“…For example, a person might ask of a new acquaintance, “Do you often organize parties?” to learn about her/his extroversion. The target of the query might answer “yes, I do,” and this response would convey a relatively different amount of information about her or his extroversion than would the answer “no, I do not.” In particular, the “yes” answer to the above question is relatively more diagnostic of the target’s extroversion (a person who often organizes parties is most likely extroverted) than is the “no” answer of the target’s introversion, because a person who does not often organize parties might still be extroverted (e.g., Brambilla, Rusconi, Sacchi, & Cherubini, 2011, Study 2; Cameron & Trope, 2004; Cherubini, Rusconi, Russo, Di Bari, & Sacchi, 2010; Rusconi & McKenzie, 2013; Rusconi, Sacchi, Toscano, & Cherubini, 2012; Sacchi, Rusconi, Bonomi, & Cherubini, 2013; Sacchi, Rusconi, Russo, Bettiga, & Cherubini, 2012; Trope & Liberman, 1996; Trope & Thompson, 1997). Therefore, the tester should revise her or his prior confidence about the target’s extroversion differently depending on whether she or he receives a “yes” or a “no” answer.…”
mentioning
confidence: 99%
“…Therefore, the tester should revise her or his prior confidence about the target’s extroversion differently depending on whether she or he receives a “yes” or a “no” answer. A fair evaluation of the answers to a question (experiment results or test outcomes) is necessary for accurate revision of initial beliefs with respect to a single hypothesis or to multiple hypotheses (Rusconi & McKenzie, 2013; Slowiaczek, Klayman, Sherman, & Skov, 1992) and, eventually, for effective decision making. The present contribution investigated which, if any, of the different normative theories advanced by statisticians, epistemologists, philosophers of science, and psychologists best described human intuition about the value of obtained evidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation